The Impact of School’s Resource Center on Teaching and Learning Process - Hamidah, Hamidah; ., Abd Razak; ., Yunus (Information Management and Business Review, 2011)
The general objective of this study is to examine the impact of School’s Resource Center (SRC) on teaching and learning process among secondary school teachers. The specific objectives are; to identify factors influencing the utilization of the SRC and the problems associated with it. In general, 100 school teachers from three secondary schools in Tanjung Malim, Perak were selected as our respondents. Sample selection was made based on purposive sampling and the data obtained were processed by using quantitative method. The results obtained reported that, on average teachers used the SRC twice a week. The reasons for the usage are; to make use the printing and non-printing media available at the SRC, and to participate in various activities and programs organized at the center. In terms of problems, there was no indication on the presence of any serious problem except the SRC should sustain its resources. In particular, the SRC must continuously upgrade the collections of printing and non-printing media with most updated and contemporary issues. Apart of that, the SRC must make available technical assistant(s) to help out the SRC users (students and teachers) anytime needed. In terms of effect, the utilization of SRC encourages group study among students and this approach not only helped to improve students understanding and to inspire their reading interest, but also offered motivation to students in understanding the content of a particular subject better.